Apatitic calcium phosphate/montmorillonite nano-biocomposite: in-situ synthesis, characterization and dissolution properties. Issue 8 (August 2022) - Jamil, M.; Elouahli, A.; Abida, F.; Assaoui, J.; Gourri, E.; Hatim, Z.
Abstract: Recently, calcium phosphate/montmorillonite composites have received attention as a synthetic bone substitutes. In this study, apatitic calcium phosphate/Montmorillonite nano-biocomposites were in-situ synthesized at 22 °C by reaction between calcium hydroxide and orthophosphoric acid in the presence of different contents of montmorillonite (MNa). Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM) and Brunauer–Emmett–Teller (BET) surface areas were used to characterize the prepared powders. The XRD results show that the composites prepared with 2 and 5 wt% MNa and sintered at 900 °C, show the formation of hydroxyapatite (HAP) structure, whereas that prepared with 10 wt% MNa leads to the formation of β-tricalcium phosphate (β-TCP) structure. The HAP structure decomposes at 1000 °C and leads to the formation of biocomposite containing HAP, β and α-TCP. However, β-TCP composites show thermal stability. FTIR and structural refinement results show the incorporation of clay ions into the apatitic structure causing changes in the crystal structure of the formed calcium phosphate phases. The changes in the composition and structure lead to an increase in the dissolution rate of HAP and a decrease in that of β-TCP. Abstract : Montmorillonite; Apatitic calcium phosphate; In-situ precipitation; Silicate biocomposites; Multiphasic biocomposite; Dissolution.